"I'm telling you my story, not publishing a blog": Considerations and suggestions on data sharing in qualitative health psychology research on sensitive topics - Gore-Gorszewska, Gabriela (Journal of health psychology, 2024)
Qualitative research plays a pivotal role in health psychology, offering insights into the intricacies of health-related issues. However, the specificity of qualitative methodology presents challenges in adhering to standard open science principles, including data sharing. The guidelines to address these issues are limited. Drawing from the author's experience in conducting in-depth interviews with middle-aged and older adults regarding their sexuality, this article discusses various challenges in implementing data sharing requirements. It emphasizes factors like participants' reasonable reluctance to share in specific populations, the depth of personal information gleaned from comprehensive interviews, concerns surrounding potential data misuse both within and outside academic circles, and the complex issue of obtaining informed consent. A universal approach to data sharing in qualitative research proves impractical, emphasizing the necessity for adaptable, context-specific guidelines that acknowledge the methodology's nuances. Striking a balance between transparency and ethical responsibility requires tailored strategies and thoughtful consideration.
Keywords: Qualitative Research; Aged; behaviorální lékařství; informovaný souhlas pacienta; informed consent; ethics; lidé; senioři; lidé středního věku; rozhovory jako téma; ženské pohlaví; Information Dissemination; Informed Consent; Sexuality; kvalitativní výzkum; Female; mužské pohlaví; qualitative methods; Behavioral Medicine; data sharing; older adults; Middle Aged; sexuality; sexualita; Interviews as Topic; Humans; Male; šíření informací